Blood : the last vampire - Chŏn, Chi-hyŏn; Miller, Allison; Cunningham, Liam; Feild, J. J. (Sony Pictures Home Entertainment, 2009)
Saya, who is half vampire and half human, uses her samurai skills to rid the world of vampires. When she is sent to an American military base in Tokyo by the organization she works for, she believes she may finally have the chance to destroy Onigen, the most evil vampire of all. Her friendship with the General's young daughter may give her the power she has needed all along - her ability for human connection.